Integrative Studies of Human Cord Blood Derived Mononuclear Cells and Umbilical Cord Derived Mesenchyme Stem Cells in Ameliorating Bronchopulmonary Dysplasia - Chen, Jia; Chen, Yuhan; Du, Xue; Liu, Guojun; Fei, Xiaowei; Peng, Jian Ru; Zhang, Xing; Xiao, Fengjun; Wang, Xue; Yang, Xiao; Feng, Zhichun (Frontiers in Cell and Developmental Biology, 2021)
Bronchopulmonary Dysplasia (BPD) is a common pulmonary complication observed in preterm infants which is composed of multifactorial pathogenesis. Current strategies, albeit successful in moderately reducing morbidity and mortality of BPD, failed to draw overall satisfactory conclusion. Herein, using a typical mice model mimicking hallmarks of BPD, we revealed that both cord blood derived mononuclear cells (CB-MNCs) and umbilical cord derived mesenchyme stem cells (UC-MSCs) are efficient in alleviating BPD. Notably, CB-MNCs infusion have more prominent effects in preventing alveolar simplification and pulmonary vessel loss, restoring pulmonary respiratory functions and balancing inflammatory responses. To further elucidate the underlying mechanisms within the divergent therapeutic effects of UC-MSC and CB-MNC, we systematically investigated the lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA networks by whole transcriptome sequencing. Importantly, pathway analysis integrating GO/KEGG/GESA method indicates that ceRNA network are mainly related to regulation of GTPase activity (GO: 0043087), ERK1 and ERK2 signal cascade (GO: 0070371) chromosome regulation (GO: 0007059) and cell cycle control (GO: 0044770). Through rigorous selection of the lncRNA/circRNA based ceRNA network, we demonstrated that the hub genes resides in UC-MSCs and CB-MNCs infused networks directed to the function of cell adhesion, motor transportation (Cdk13, Lrrn2) and immune homeostasis balance, autophagy (Homer3, Prkcd) relatively. Our studies illustrate the first comprehensive mRNA-miRNA-lncRNA and mRNA-miRNA-circRNA networks in stem cells infused BPD model, which will be valuable in identifying reliable biomarkers or therapeutic targets for BPD pathogenesis and shed new light in the priming and conditioning of UC-MSC or CB-MNC in treatment of neonatal lung injury.